A derivative of 2-aminothiazole inhibits melanogenesis in B16 mouse melanoma cells via glycogen synthase kinase 3 beta phosphorylation - Kim, Su Yeon; Hahn, Hoh-Gyu; Nam, Kee Dal; Park, Kyoung-Chan; Yun, Hye-Young; Baek, Kwang Jin; Kwon, Nyoun Soo; Kim, Dong-Seok (WILEY-BLACKWELL, 2011)
Objectives We have investigated whether KHG25855 (2-cyclohexylamino-1,3-thiazole hydrochloride) affected melanogenesis in B16 mouse melanoma cells, and the mechanisms involved. Methods Melanin content and tyrosinase activity were measured using an ELISA reader after cells were treated with KHG25855. KHG25855-induced signalling pathways were examined using Western blot analysis. Key findings KHG25855 decreased melanin production in a dose-dependent fashion, but KHG25855 did not directly inhibit tyrosinase, the rate-limiting melanogenic enzyme. The expression of microphthalmia-associated transcription factor, tyrosinase, and the related signal transduction pathways were also investigated. The effects of KHG25855 on the extracellular signal-regulated kinase and cAMP response element binding protein signalling pathways were determined, and KHG25855 was shown to have no effect on these signalling pathways. The Wnt signalling pathway is also deeply involved in melanogenesis, and so glycogen synthase kinase 3 beta (GSK3 beta) phosphorylation was assessed after KHG25855 treatment; KHG25855 caused GSK3 beta phosphorylation (inactivation), but the level of beta-catenin was not changed by KHG25855. Furthermore, alpha-melanocyte stimulating hormone-induced tyrosinase expression was downregulated by KHG25855. Conclusions We propose that KHG25855 showed hypopigmentary activity through tyrosinase downregulation via GSK3 beta phosphorylation.
Keywords: NORMAL HUMAN MELANOCYTES; SKIN PIGMENTATION; GENE-EXPRESSION; CYCLIC-AMP; MITF; CAMP; ACTIVATION; PATHWAY; AKT; MICROPHTHALMIA